2022
DOI: 10.1097/olq.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cefixime for the Treatment of Neisseria gonorrhoeae Infection at 3 Anatomic Sites: A Systematic Review and Meta-Analysis

Abstract: Background: To treat Neisseria gonorrhoeae infection, the Centers for Disease Control and Prevention recommends a single oral dose of cefixime as an alternative to injectable ceftriaxone. Methods:We conducted a systematic review and meta-analysis to describe the effectiveness of cefixime in treating N. gonorrhoeae infection at 3 different anatomic sites.We searched PubMed and Embase database to abstract treatment success rates and cefixime dosage/frequency for studies that reported the anatomical site of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 29 An Australian study found that people who abuse alcohol had a 1.6 times higher risk of contracting gonorrhea compared to people who did not abuse alcohol. 50 Given the consequences of untreated gonorrhea and the relative ease of treatment, 51 the CAGE questionnaire could be used as a tool for identifying people at risk who may benefit from further screening to receive earlier treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 29 An Australian study found that people who abuse alcohol had a 1.6 times higher risk of contracting gonorrhea compared to people who did not abuse alcohol. 50 Given the consequences of untreated gonorrhea and the relative ease of treatment, 51 the CAGE questionnaire could be used as a tool for identifying people at risk who may benefit from further screening to receive earlier treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The 800 mg oral dose of cefixime should only be considered as an alternative therapy to cephalosporins because it does not provide as high or sustained blood bactericidal levels as ceftriaxone 500 mg IM [ 32 ]. It also shows limited efficacy for treating of pharyngeal gonorrhea (81% cure, 95% confidence interval 61%–92%) [ 33 ]. In particular, sensitivity of gonorrhoeae isolated in Korea to cefixime decreased from 91% in 2018 to 77% in 2019 [ 30 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This antibiotic is oftentimes used for the therapeutic management of cutaneous or skin infections and its associated conditions such as acne vulgaris [77][78][79] as well as sexually transmitted infections (STIs), such as gonorrhea, caused by the pathogenic Gram-negative bacteria Neisseria gonorrhoeae [80,81], either on its own or in combination with other medications such as gemifloxacin, gentamicin, and extended-spectrum cephalosporins [82][83][84]. Cefixime (as an alternative to ceftriaxone) is another well-known antibiotic that is utilized for the treatment of gonorrhea and is also efficacious against a vast array of both Gram-positive and Gram-negative bacteria, such as all strains of group A Streptococci, Haemophilus influenzae, E. coli, and Moraxella catarrhalis, regardless of their β-lactamase production status, as well as strains of pneumococci that are penicillin sensitive [85][86][87]. Clindamycin is a medication used for the treatment of skin and skin structure infections as well as intra-abdominal infections, lower respiratory, gynecological, bone and joint infections, and septicemia [88].…”
Section: Comparison Of the Efficacy Of R Ferrugineus Larvae With Othe...mentioning
confidence: 99%